Effectiveness of Combined Guided Imagery and Relaxation Music Therapy in Reducing Post-Cesarean Section Pain: A Quasi-Experimental Study - Rana Zahrah Afifah; Sulastri Sulastri (Jurnal Ners, 2026)
Background: Sectio caesarea (SC) is a surgical procedure that often causes postoperative pain due to tissue damage and the wound-healing process. Unmanaged pain can hinder mobilization, recovery, and a mother's ability to care for her newborn. One of the non-pharmacological therapies that can be used to help reduce pain is the combination of guided imagery and relaxation music. Objective: To determine the effect of a combination of guided imagery and relaxation music on pain levels among post-sectio caesarea patients at Jendral Ahmad Yani Regional General Hospital, Metro City. Methods: This study employed a pre-experimental design using a one-group pretest-posttest approach. The research was conducted in the maternity ward of Jendral Ahmad Yani Regional General Hospital, Metro City, from May to July 2026. The sample consisted of 32 respondents selected through purposive sampling according to the inclusion and exclusion criteria. Pain levels were measured using the Numeric Rating Scale (NRS). Data were analyzed using the Wilcoxon Signed Rank Test because the data were not normally distributed based on the Shapiro–Wilk normality test. Results: The characteristics of respondents showed that most were aged 21–35 years (65.6%), had a senior high school education (68.8%), and were employed (53.1%). Before receiving the combination of guided imagery and relaxation music, most respondents experienced moderate pain (75.0%). After the intervention, most respondents experienced mild pain (71.9%). The Wilcoxon test results showed a p-value of 0.000 (<0.05), a Z value of -4.762, and a mean rank of 15.00, indicating a significant effect of the combination of guided imagery and relaxation music on reducing pain levels among post-sectio caesarea patients. Conclusion: The combination of guided imagery and relaxation music has a significant effect on reducing pain levels among post-sectio caesarea patients at Jendral Ahmad Yani Regional General Hospital, Metro City. This intervention can be considered a complementary non-pharmacological therapy in postoperative pain management for sectio caesarea patients.